Evaluation of the Linking Systems of Care for Children and Youth Demonstration Project, Illinois, Montana, Ohio, and Virginia, 2015-2019 - Haas, Stephen ([Verlag nicht ermittelbar], 2023)
The victimization of children and youth remains a nationwide concern with between 44 percent and 60 percent of children reporting experiences of victimization in national studies. The impacts of victimization, if left unaddressed, can have serious long-term effects on the physical and mental health of children, which vary based on the children's developmental stage and frequency of exposure. The high rates of victimization, coupled with the serious negative consequences of the victimization, underscore the importance of ensuring effective service delivery to meet the needs of this population. Building on decades of work in social change in organizations and communities, the Office for Victims of Crime (OVC), under the United States Department of Justice Strategic Initiative, sought to address the needs of victims of crime. As part of the Strategic Initiative, OVC created the Linking Systems of Care (LSC) for Children and Youth State Demonstration Project, a project intended to directly impact the field of child victimization by bringing together all of the relevant systems and professionals to provide early identification, intervention, and treatment for child and youth victims and their families and caregivers.